2020
DOI: 10.1002/da.23029
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, controlled, participant‐ and rater‐blind trial of pharmacogenomic test‐guided treatment versus treatment as usual for major depressive disorder

Abstract: Background Cohort and cost‐effectiveness studies suggest that measuring variation in genes that influence metabolism of common drugs could improve antidepressant treatment outcomes. Prior randomized trials have yielded inconsistent results. Method Multicenter randomized double‐blind (subject and rater), controlled trial of pharmacogenomic testing among outpatients with nonpsychotic major depressive disorder. Study participants (n = 304) were randomized 1:1 to assay‐guided treatment (AGT; N = 151) or treatment‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 13 publications
1
75
0
Order By: Relevance
“…Thus, biases (e.g., expectancy bias and performance bias) may have influenced results. Blinding of participants, outcome assessors, as well as prescribers 19 would buoy these results in future replications. Notably, the current investigation did not find expected differences in treatment satisfaction across groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, biases (e.g., expectancy bias and performance bias) may have influenced results. Blinding of participants, outcome assessors, as well as prescribers 19 would buoy these results in future replications. Notably, the current investigation did not find expected differences in treatment satisfaction across groups.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed effect models have been applied in recent investigations of pharmacogenomics guided treatment. 19 This analysis approach handles missing values using maximum likelihood estimation, which is able to use all available information in all recruited participants, and is associated with the least bias in a comparison of methods for dealing with missing data. 38 We followed the intention‐to‐treat principle and analyzed all randomized participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two meta-analytic evaluations of the clinical efficacy of commercial PGx testing in psychiatry have been conducted for prospective and retrospective clinical trials and showed that testing improves the likelihood of achieving symptom remission compared to treatment as usual [85,86]. However, recent inconclusive or negative trial findings have been reported [87,88], leading some to conclude that commercial PGx testing is not ready for widespread use in psychiatry This document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.…”
Section: Test Clinical Efficacy and Cost-effectivenessmentioning
confidence: 99%
“…Two meta-analytic evaluations of the clinical efficacy of commercial PGx testing in psychiatry have been conducted for prospective and retrospective clinical trials and showed that testing improves the likelihood of achieving symptom remission compared to treatment as usual [85,86]. However, recent inconclusive or negative trial findings have been reported [87,88], leading some to conclude that commercial PGx testing is not ready for widespread use in psychiatry [89]. Furthermore, evidence of clinical efficacy has primarily been constrained to adults of European-ancestry with major depressive disorder who had a history of antidepressant non-response or adverse drug reactions, suggesting evaluations of clinical efficacy in other clinical populations (e. g., non-Europeans, treatment-naïve, children, schizophrenia) are required.…”
Section: Test Clinical Efficacy and Cost-effectivenessmentioning
confidence: 99%